Design of a Free Nutritious Food Menu Preparation System with Interactive Nutrition Calculation Simulation - Muhammad Romadhona Kusuma (Journal of Innovation and Computer Science, 2025)
The government's preparation of free nutritious food menus represents a strategic initiative to improve public health, particularly for vulnerable populations such as underprivileged families. This study presents a web-based simulation system designed to assist the government in planning menus with processes that are not only quantitatively adequate but also aligned with balanced nutritional standards. The platform enables users to select food ingredients based on specific nutritional targets, including calories, carbohydrates, protein, and fat. To ensure that each stage—ingredient selection, nutrition calculation, validation, and result presentation—proceeds in a structured and efficient sequence, the system adopts a Finite State Automata (FSA) approach. Implementation results demonstrate that the system can accurately compute and visualize nutritional values using interactive pie charts, helping users evaluate the nutritional balance of selected menus. The key contribution of this study lies in integrating the FSA method to structure the menu preparation process, combined with interactive data visualization techniques to enhance user comprehension. This approach aims to improve public nutritional literacy and ensure that distributed meals deliver optimal health benefits.